Finding Harmony between Decolonization and Christianity in Academia - Fainga'a-Manu Sione, Inez; Faleolo, Ruth (Lute); Hafu-Fetokai, Cathleen (Art/Research International)

(untitled) (University of Alberta, 2024)
This article presents our theoretical musings on practicing decolonization as Christian Tongan academics, recorded and shared within our Australian collective during 2022-2023. We aim to discuss the strength and power that comes from our Indigenous inheritance of God and Tonga, living in diaspora of Australia and Aotearoa New Zealand (tu'a Tonga). Amidst this Indigenous strength, there are also subtleties and crescendos of coloniality taking place in and around us, as well as the complexities and vulnerabilities with which Tongan Christian academics grapple in their sense making and meaning making processes. The significance of this discussion is that Oceanian women’s opinions and experiences of decoloniality are not often considered, particularly within the contexts of academia. We pray this article offers insights into how we can successfully navigate simultaneous private, public, individual, and collective journeys, daily, as Christian academics in the decolonization of these various spaces. This is our contribution as Christian academics, as daughters of Tonga, and wives and mothers of Oceania.